2013
DOI: 10.1103/physreva.88.052505
|View full text |Cite
|
Sign up to set email alerts
|

Satellite and hypersatellite structures ofLα1,2andLβ1x-ray transitions in mid-et al.

Abstract: A detailed investigation of the Lα 1,2 (L 3 →M 4,5) and Lβ 1 (L 2 →M 4) x-ray satellite and hypersatellite structures in zirconium, molybdenum, and palladium atoms multiply ionized by impact with 278.6-MeV oxygen ions is reported. The x-ray spectra were measured with a high-resolution von Hamos bent crystal spectrometer. For the interpretation of the complex spectral features, relativistic multiconfiguration Dirac-Fock calculations were performed for all multivacancy configurations expected to contribute to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The energy stability of inner-shell electrons was experimentally observed for Lα x-ray emission for different oxidation states [53,54]. It is reported that even Nsatellites lines are reported to be within the linewidth of the Lα x-ray emission line [55] and only M -shell satellites lines will be outside the Lα emission linewidth. However, appearance of M -satellites lines would indicate presence of three-photon absorption process within the M corehole lifetime which, according to the power law of nth order process 10 −33 cm 2n s n−1 [56], will be of much lower probability than the two-photon absorption.…”
Section: Experimental Considerationmentioning
confidence: 98%
“…The energy stability of inner-shell electrons was experimentally observed for Lα x-ray emission for different oxidation states [53,54]. It is reported that even Nsatellites lines are reported to be within the linewidth of the Lα x-ray emission line [55] and only M -shell satellites lines will be outside the Lα emission linewidth. However, appearance of M -satellites lines would indicate presence of three-photon absorption process within the M corehole lifetime which, according to the power law of nth order process 10 −33 cm 2n s n−1 [56], will be of much lower probability than the two-photon absorption.…”
Section: Experimental Considerationmentioning
confidence: 98%
“…Line spectra are regularly analysed using the Voigt functions when Lorentzian and Gaussian widths are comparable. For example, using a high-resolution crystal diffractometer, accurate measurements were made of diagram lines and of multiple-satellite, hypersatellite and hypersatellite-satellite L α1 and L α2 X-ray lines of palladium [12], of L α1,2 and L β1 X-ray lines of zirconium, molibdenum and palladium [13], and of thorium L γ Xray lines [14], produced by heavy-ion (O 6+ ) beams of 278.6 MeV. To interpret the observed spectra, relativistic multiconfigurational Dirac-Fock calculations were made for the lines with variable numbers of L-and M -shell vacancies.…”
Section: Introductionmentioning
confidence: 99%